(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
The concept of e-tax filing is introduced by the e-government that motivates the use of ICT (information and communication technology), specifically they focus on the usage of the internet-related application to run an activity. The current study is aimed to understand the acceptance of e-tax by the consumers. The impact of attitude towards adopting e-tax, subjective norm, perceived behavioural control on intention of electric e-tax. The current study uses the close-ended questionnaire to conduct the survey and to collect the responses from the contributors. The total number of a questionnaire that was supposed to be filled by the participant was 193. All the construct uses a five-point Likert scale. All variables of TPB are regressed with adoption intention to analyse whether TPB variables have any significant impact on adoption intention. Thus we can conclude that H1, H2 and H3 of the current study are accepted. A future researcher should examine the other factors that may influence the etax adoption. This study is limited to the Iraqi context, other nation’s dimension must also be analysed. A future researcher should also examine the culture-specific and cross-culture factors in their researchers. Future study should also focus on the relationship among the component so that they can achieve higher explanation power and lastly, a researcher should also examine the variation in the subjective norms, attitude and control behaviour across primary adoption and extension stages.